2014
DOI: 10.3233/bme-141055
|View full text |Cite
|
Sign up to set email alerts
|

Study of parameters for evaluating flow reduction with stents in a sidewall aneurysm phantom model

Abstract: The effect of stent design parameters such as porosity, pore density, number of strands, and strut angle to the artery were studied in vitro using particle image velocimetry (PIV). Five mesh stents were implanted into a sidewall aneurysm model. The flow features in a sidewall aneurysm silicone phantom model were investigated at a Reynolds number of 300. It was found that the lowest porosity stent had the best value for velocity and vorticity reduction in an aneurysm pocket. The stent with higher pore density h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
(12 reference statements)
1
9
0
Order By: Relevance
“…Raben et al observed that wider bifurcation angles increases area of low flow and recirculation [ 42 ], while Yu and Kwon observed that endovascular prosthesis’s design parameters such as number of strands, or strut angle have also significant influence on implant’s migration risk. They also observed that an ideal endovascular prosthesis should have higher strut angle [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Raben et al observed that wider bifurcation angles increases area of low flow and recirculation [ 42 ], while Yu and Kwon observed that endovascular prosthesis’s design parameters such as number of strands, or strut angle have also significant influence on implant’s migration risk. They also observed that an ideal endovascular prosthesis should have higher strut angle [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Flow diverter-equivalent porosities can induce near-stagnant flows in sidewall and/or low flow aneurysms, while the flow reductions in bifurcation and/or high-flow patient geometries are comparatively less. Increasing the device pore density while maintaining a constant porosity also results in reduced intraneurysmal flow activity [7,15,[40][41][42]. Again, there is a wide variation in the results thus far and a very loose extrapolation from these studies on simplified geometries suggests that doubling the pore density (at constant porosity) can result in reduction of flow activity ranging anywhere between 20% and 150%.…”
Section: Intra-aneurysmal Flow Alterationsmentioning
confidence: 99%
“…3,[9][10][11][12][13][14][15][16][17][18] In general, it is well established that lowering the device porosity and increasing the device pore density results in greater reduction of intraneurysmal flow activity. 11,13,16,[19][20][21][22][23][24][25][26] The primary clinical utility of all these studies is to be able to predict device efficacy (long-term aneurysm occlusion) based on intraneurysmal flow reduction quantities. Sample sizes are sparse, but several studies based on clinical data [27][28][29][30][31][32][33] collectively note that the reduction in intraneurysmal flow after flow diversion can be significantly different between aneurysms that remain patent at follow-up versus those that occlude at follow-up; the sensitivity and specificity of these parameters seem reasonably high at 75%-90%.…”
Section: Introductionmentioning
confidence: 99%